Examining students’ Self-Assessment of Digital Argumentation (SADA) in e-biology class: A Rasch analysis - Marheny Lukitasari; Jeffry Handika; Wasilatul Murtafiah; Agita Risma Nurhikmawati (JPBI (Jurnal Pendidikan Biologi Indonesia), 2020)
Self-Assessment of Digital Argumentation (SADA) is considerable instrument to assess students’ digital argumentation (DA) in e-learning model.  The research objectives were: (1) to investigate how SADA can be used as an instrument for assessing students’ DA; and (2) to access students’ DA through SADA in e-Biology class. The study population was 132 students of Biology Education Department of UNIPMA in which the 64 students as the samples were taken purposively. The instrument used was the SADA questionnaire. The data were analyzed using Rasch model. The statistical summary showed that the interaction between respondents and items was very good (Cronbach alpha was 0.95 > 0.8). Meanwhile, the person reliability (0.92) and item reliability (0.75) were categorized as were categorized as "good". This study also revealed that there were 26.69% of students classified as having high DA, 40.63% have a moderate DA, and 29.69% have a low DA. This research proves that SADA can be used to measure students' self-assessment in doing their DA during e-learning. SADA also helps students evaluate their own learning process.